Socio-Economic Growth Model Agglomerations: Practice and Prospects for Development - A., Tovma N.; A., Hajek P. (Farabi Journal of Social Sciences, 2019)
Abstract. The new millennium has been proclaimed one of the cities. Issues of urbanization have become relevant in connection with tasks of entering of Kazakhstan among the 30 years of highly developed countries of the world. In The President of Kazakhstan, Nursultan Nazarbayev the people speak on the need to ensure the development of an infrastructure of the triad-centres, transport, energy. Agglomeration is the skeleton of the knowledge economy. Research methodology is based on a combination of methods: mathematical modeling, statistical groupings of sociological research methods.